EFEKTIVITAS SENYAWA AKTIF DAUN SELASIH SEBAGAI PENGENDALI Aphid Spp - Tyas Soemarah Koernia Dewi; Endang Suprapti; DARYANTI DARYANTI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
Basil (Ocimum basillicum) is one of plant which can be used for biopesticide. The research was carried out at Balai Penelitian Tanaman Obat Tawangmangu ( BPTOT ) and Faculty of Agriculture Tunas Pembanguan University, Surakarta, to find out sum of actif compound of basil, dose and consentration effective for controlled Aphid Spp. on red pepper chili. The result of chromatographi analist showed that volatile oil 0,560%, yellow, geraniol 20,00%, methyl eugenol 30,04%, and sitrol 41,45%. Based of that result, carry out to controlled Aphid Spp. on red pepper chili at Green House Faculty of Agriculture, Tunas Pembangunan University, Surakarta. The parameters were population of Aphid Spp., attact intensity, height of plant, weight of fresh crown, weight of dry crown, sum of red pepper chili, sum of green pepper chili, weight of red pepper chili, and weight of green pepper chili. The result showed that dose and consentration of active compound of basil significant fot attact intensity and weight of red pepper chili.